Cysteine Aminotransferase (CAT) - Hipólito, Ana (2020)
Metabolic remodeling is a critical skill of malignant cells, allowing their survival and spread. The metabolic dynamics and adaptation capacity of cancer cells allow them to escape from damaging stimuli, including breakage or cross-links in DNA strands and increased reactive oxygen species (ROS) levels, promoting resistance to currently available therapies, such as alkylating or oxidative agents. Therefore, it is essential to understand how metabolic pathways and the corresponding enzymatic systems can impact on tumor behavior. Cysteine aminotransferase (CAT) per se, as well as a component of the CAT: 3-mercaptopyruvate sulfurtransferase (MST) axis, is pivotal for this metabolic rewiring, constituting a central mechanism in amino acid metabolism and fulfilling the metabolic needs of cancer cells, thereby supplying other different pathways. In this review, we explore the current state-of-art on CAT function and its role on cancer cell metabolic rewiring as MST partner, and its relevance in cancer cells' fitness.